An Arena Simulation Model For Empty Container Reposition Problems - LIU, CHIA-HAO (2012)
The imbalance in international trading has deeply affected shipping lines’ income. Due to this shipping lines have started to focus on container reposition problems to enhance their competitive strength. However, according to research report from Crinks (2000), the author points out that in global container utilization, a large percentage is used for idle and empty container repositioning. In addition, container reposition operations rely on operators’ experiences and historical data. It is clear that shipping lines bear large uncertain risks in the process. Many researchers believe that container reposition problems involve many factors, thus, constructing an operation model which can support operators is an essential process.